Analisis Penilaian Aspek Green Hotel di Hotel Vertu Harmoni Jakarta - Nathan Lay, Nathan Lay; Yudhiet Fajar Dewantara, Yudhiet Fajar Dewantara (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the assessment of the implementation of the concept of implementing green hotel or hotel that are environmentally friendly at the Vertu Harmoni Jakarta hotel. The type of research used is qualitative in this study. Interviews and observations using survey methods and analysis used in this study are regression models simple. The results of the study show that hotel have started to try to implement the concept of green hotel or hotel that are environmentally friendly in their hotel operations. Hotel Vertu Harmoni Jakarta has also implemented innovations and programs that help address the surrounding environment and help in the environmental management process. The hope is that the hotel can become a hotel that can apply the concept of an environmentally friendly hotel without any loss on either side, either from the guests or hotel visitors or the hotel.